Above-knee prosthesis design based on fatigue life using finite element method and design of experiment - Suwattanarwong Phanphet (2018)
© 2017 IPEM The main objective of this work is to improve the standard of the existing design of knee prosthesis developed by Thailand's Prostheses Foundation of Her Royal Highness The Princess Mother. The experimental structural tests, based on the ISO 10328, of the existing design showed that a few components failed due to fatigue under normal cyclic loading below the required number of cycles. The finite element (FE) simulations of structural tests on the knee prosthesis were carried out. Fatigue life predictions of knee component materials were modeled based on the Morrow's approach. The fatigue life prediction based on the FE model result was validated with the corresponding structural test and the results agreed well. The new designs of the failed components were studied using the design of experimental approach and finite element analysis of the ISO 10328 structural test of knee prostheses under two separated loading cases. Under ultimate loading, knee prosthesis peak von Mises stress must be less than the yield strength of knee component's material and the total knee deflection must be lower than 2.5 mm. The fatigue life prediction of all knee components must be higher than 3,000,000 cycles under normal cyclic loading. The design parameters are the thickness of joint bars, the diameter of lower connector and the thickness of absorber-stopper. The optimized knee prosthesis design meeting all the requirements was recommended. Experimental ISO 10328 structural test of the fabricated knee prosthesis based on the optimized design confirmed the finite element prediction.